MANAJEMEN KURIKULUM BERBASIS KARYA MANDIRI DALAM MEMBANGUN KREATIVITAS ANAK DIDIK - Ina Suryanti; Nurul Ulfatin; Ali Imron; Ina Suryanti; Nurul Ulfatin (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine independent work-based curriculum management,efforts to build students' creativity and student characteristics. This study uses aqualitative method with a type of case study. Data collection was carried out byinterview, observation, and documentation. The findings of this study include thecurriculum management process of independent work, independent workproduced by students and the characteristics or creativity of early childhood